DEVELOPMENT OF AISAS MODEL TO SEE THE EFFECT OF TOURISM DESTINATION IN SOCIAL MEDIA - Abdurrahim, Muhamad Syahid; Najib, Mukhamad; Djohar, Setiadi (Jurnal Aplikasi Manajemen, 2019)
The development of information technology is growing rapidly, one proof of the rapid progress of information technology is the development of social media. Promotion on social media is a popular way for companies, even government agencies. The purpose of this study was to see the effect of the promotion of tourist destinations on social media by developing the Aisas model to see the relationships between the verbs in it. The analytical method used in this study uses Structural Equation Modeling (SEM) which is run using LISREL software. The results of the study show that promotion on social media has a significant effect on one’s attention, interest, and desire to find more information about the information being promoted. And one’s attention and interest have a significant influence on tourism decisions. A person’s tourism activities influence the desire to share his travel experience. Further research is expected to be able to examine the trends of social media that are most effectively used for promotion.